Trend Analysis of the Profiles of 12 Sexually Transmitted Disease Pathogens in the Republic of Korea in 2019. (16th December 2021) - Park, Hye-Jee; Kim, Yun-Tae; Moon, Ju Young; Jin, Choong Eun; Ko, Ki-Han; Lee, Seung-hyun; Min, Okgi; Je, Young Soo; Lee, Mikyeong; Lee, Sanghoo; Kim, Young-Jin; Lee, Kyoung-Ryul
Background: Sexually transmitted diseases (STDs) are common infectious diseases in humans transmitted through unprotected sexual activities. In South Korea, despite the high annual incidence of STDs, detailed examinations of pathogen-specific factors and causes for delays in diagnosis and treatment are still lacking. Furthermore, STD prevalence patterns and important pathogen-specific factors remain unclear. Herein, we retrospectively analyzed the epidemiology of STDs in South Korea in 2019 by analyzing the association of pathogen-specific infection patterns with factors such as sex, age, region, and month. Methods: We obtained the STD test results of 172, 973 individuals from the Seoul Clinic Laboratory in 2019, most of whom had multiple infections; hence, 275, 296 STD-positive cases were included in this analysis. Through deoxyribonucleic acid (DNA) amplification, they were categorized by pathogen type. Subsequently, they were further classified by month, region, and age while concurrently being stratified according to sex. Results: Among the 12 pathogens detected in this study, Gardnerella vaginalis had the highest prevalence, with 92, 490 cases in both sex groups; moreover, many of them were concurrently infected by two or more pathogens. The prevalence of STDs did not differ according to month or region. Conversely, the pathogen-specific prevalence rates significantly differed according to age. Older adults had higher prevalence rates of Chlamydia trachomatis, Trichomonas vaginalis, Candida albicans, and herpes simplex virus type 1 infections than younger adults. Conclusion: These pathogen-specific prevalence patterns provide information that helps to understand population vulnerability according to region and age and helps develop STD prevention and treatment strategies in South Korea.